A systems model for commercialising emerging technology: wave energy farm system (WEFS) case study. (1st January 2013) - Bonilla, Oscar; Merino, Donald N.; Raftery, Michael; Wainer, Tamara; Jain, Rashmi
This paper proposes a systems life cycle model that could be used to analyse the commercial feasibility of emerging technologies development. The model is based on a comprehensive review of the literature on the key factors impacting the success or failure in commercialising technology. The proposed systems model includes a technical, economic and operational domain and covers a project's planning, project implementation and feedback, analysis and control phases. This model was applied to a case study, a wave energy technology, with a concentration on the economic domain. The economic domain includes an after tax analysis model, which a typical company uses to assess economic feasibility and a sensitivity analysis that identifies the most important attributes. The internal rate of return (IRR) and other figures of merit (FoMs) were used to show whether the project meets standard business criteria. This case shows how financial leverage significantly improves a project's economic attractiveness.